Targeting Anion Exchange of Osteoclast, a New Strategy for Preventing Wear Particles Induced- Osteolysis - Wu, Chuanlong; Liu, Xuqiang; Sun, Ruixin; Qin, Yunhao; Liu, Zhiqing; Yang, Shengbing; Tang, Tingting; Zhu, Zhenan; Yu, Degang; Liu, Fengxiang (Frontiers in Pharmacology, 2018)
Joint replacement is essential for the treatment of serious joint disease. However, prosthetic failure remains an important clinical issue, with periprosthesis osteolysis (PO), caused by osteoclastic bone resorption induced by wear particles, being the leading cause of failure. Nuclear factor of activated T cells c1 (NFATc1) appears to play an important role in wear particle-induced osteoclastogenesis, with bicarbonate/chloride exchanger, solute carrier family 4, anion exchanger, member 2, (SLC4A2) being upregulated during osteoclastogenesis in an NFATc1-dependent manner. Anion exchange mediated by SLC4A2 in osteoclasts could affect the bone resorption activity by regulating pHi. This study investigated the role and mechanism of SLC4A2 in wear particle-induced osteoclast differentiation and function in vitro. The use of 4, 4'-diisothiocyano-2, 2'-stilbenedisulfonic acid (DIDS), an anion exchange inhibitor, suppressed wear particle-induced PO in vivo. Furthermore, controlled release of DIDS from chitosan microspheres can strengthen the PO therapy effect. Therefore, anion exchange mediated by osteoclastic SLC4A2 may be a potential therapeutic target for the treatment of aseptic loosening of artificial joints.